3x

(3x-7)(x-2) = 0 (factor the expression)

Roots are found by setting the factors to zero.

(3x-7) = 0

3x = 7

x = 7/3

x-2 = 0

x = 2

_____

Factoring this expression can be somewhat tricky. You need to look at the factors of 3 and of 14.

14 = 1*14 = 2*7

3 = 1*3

Because the sign of 14 is positive and the sign of 13 is negative, the sign of the constant in each binomial factor will be negative. The product of one pair of factors will be added to the product of the other pair of factors to get -13. So, we choose 1*(-7) and 3*(-2) to get -7 -6 = -13.

^{2}- 13x + 14 = 0(3x-7)(x-2) = 0 (factor the expression)

Roots are found by setting the factors to zero.

(3x-7) = 0

3x = 7

x = 7/3

x-2 = 0

x = 2

_____

Factoring this expression can be somewhat tricky. You need to look at the factors of 3 and of 14.

14 = 1*14 = 2*7

3 = 1*3

Because the sign of 14 is positive and the sign of 13 is negative, the sign of the constant in each binomial factor will be negative. The product of one pair of factors will be added to the product of the other pair of factors to get -13. So, we choose 1*(-7) and 3*(-2) to get -7 -6 = -13.